EFFECT OF DIAMETRAL TENSILE STRENGTH OF BULK FILL COMPOSITE RESIN WITH THE ADDITION OF SUGARCANE WASTE FIBER - Isyana Erlita; Yusuf M. Hernandi; Muhammad Yanuar Ichrom Nahzi (Dentino : Jurnal Kedokteran Gigi, 2018)
Backgrounds: Bulk fill composite resin is a composite resin type which can be polymerized as deep as 4 mm and is indicated for posterior tooth restoration. Most posterior tooth restorations become fractured because of the composite resins that are not able to withstand the tensile stress that happens. Efforts to increase diametral tensile strength is by adding fiber. The use of natural fibers can be an alternative because it is environmentally friendly and inexpensive. One of the natural fibers is fiber bagasse (Saccharum Officinarum L.). Purpose: To know the influence of composite resin diametral tensile strength value in bulk fill  with the addition of bagasse fiber. Methods: Experimental laboratory studies with post-test designs only with control group designs. The experiment of consist 36 samples which divided into 3 groups. Group I non-fiber bulk fill resin composite, group II filling composite with bagasse fibers and group III filling composite resins with glass fibers as a control group. The sample are immersed in saline solution and incubated for 24 hours at 37° C. Then sample tested its diametrically tensile strength using a Universal Testing Machine. Data analysis used One Way Anova test with significance value of 0,001 (p<0,05), followed by Post Hoc Bonferroni. Results: Post Hoc Bonfferoni test obtained p value= 0.001 (p<0.05), which means there are significant differences between the three groups where the group with the addition of glass fiber obtained the highest diametral tensile strength value. Conclusion: the addition of bagasse fiber affects the diametral tensile strength and can increase the diametral tensile strength of the bulk fill composite resin.